2013
DOI: 10.1109/lawp.2013.2296560
|View full text |Cite
|
Sign up to set email alerts
|

User Effects in Beam-Space MIMO

Abstract: The performance and design of the novel single-RF-chain beam-space MIMO antenna concept is evaluated for the first time in the presence of the user. First, the variations of different performance parameters are evaluated when placing a beam-space MIMO antenna in close proximity to the user body in several typical operating scenarios. In addition to the typical degradation of conventional antennas in terms of radiation efficiency and impedance matching, it is observed that the user body corrupts the power balan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…The basis correlation is also increased to −11.9 dB in the worst case, which is still sufficiently good for MIMO operation. As concluded in [5], the impairments of the power imbalance ratio and the basis decorrelation show a less pronounced degradation effect on the multiplexing performance of the beam-space MIMO systems.…”
Section: Simulation Results and Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The basis correlation is also increased to −11.9 dB in the worst case, which is still sufficiently good for MIMO operation. As concluded in [5], the impairments of the power imbalance ratio and the basis decorrelation show a less pronounced degradation effect on the multiplexing performance of the beam-space MIMO systems.…”
Section: Simulation Results and Discussionmentioning
confidence: 78%
“…It has been shown that although the near-field interaction with transmit antennas in beam-space MIMO deteriorates the orthonormality of the basis patterns, throughput reduction is still mainly caused by the power absorption in user body tissues rather than by the distortion of the basis characteristics. While the conclusion in [5] confirms the suitability of using beam-space MIMO in near-field interaction scenarios under BPSK modulation, it cannot immediately be generalized to higher-order modulation schemes, where the external perturbation also causes the actual constellation points to deviate from their ideal locations, assumed when decoding under the assumption of a conventional MIMO system model. Such degraded modulation quality can then result in a bit error rate (BER) performance degradation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…지 문제점이 발생할 수 있다 [7] . 시스템에서 RF 단이 증가할수록 전체적인 시스템 복잡도가 증가하게 되고 이로 인하여 전력 소비 또한 급증하게 된다 [7] . 또한 RF 단이 증가하게 되면 RF 단간 간섭이 발생하여 전 체적인 시스템의 성능을 열화 시킬 수 있다.…”
Section: 또한 현재 폭발적인 관심을 받고 있는 5gunclassified
“…또한 RF 단이 증가하게 되면 RF 단간 간섭이 발생하여 전 체적인 시스템의 성능을 열화 시킬 수 있다. 마지막으 로 RF 단의 증가는 전체적인 시스템 구성의 비용을 크게 증가시키게 된다 [7] . 이러한 RF 단의 증가에 따른 문제점을 해결하기 위하여 다양한 연구들이 진행되고 있다.…”
Section: 또한 현재 폭발적인 관심을 받고 있는 5gunclassified